Z.N. Gippius’s Letters to F.A. Chervinsky - Alexander L. Sobolev (Russian Academy of Sciences. A.M. Gorky Institute of World Literature, 2021)
The publication introduces 33 letters of the 1890s from Z.N. Gippius to the writer, poet and playwright, St. Petersburg lawyer F.A. Chervinsky. Gippius’s short romance with Chervinsky, as happened with her other heartfelt passions, provoked an intense epistolary dialogue, avoiding, however, direct expression and self-reflection of feelings. Gippius's letters are dominated by playing and light coquetry, full of hints and provocations, and the life romance itself is built by her as a tense psychological experiment. Their relationship in 1892 –1893 found reflection in the works of both participants — in Gippius's fairy tale “Time” and Chervinsky's story “Sylphide”, typical examples of modernist interrelation of literature and life. At the same time, the letters are interesting for the details of literary events reported in them, for the characteristics of a number of contemporary writers — N. Minsky, D. Merezhkovsky, A.P. Chekhov and other common acquaintances.